2008
DOI: 10.1007/s10886-008-9441-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential Chemosignals in the Anogenital Gland Secretion of Giant Pandas, Ailuropoda melanoleuca, Associated with Sex and Individual Identity

Abstract: With a combination of dichloromethane extraction and analysis by gas chromatography-mass spectrometry (GC-MS), we found 39 compounds (corresponding to 38 GC peaks) in the anogenital gland secretion (AGS) of captive adult giant pandas, Ailuropoda melanoleuca, during the non-mating season. In addition to indole, squalene, and some of the straight-chain fatty acids that had been characterized previously from the AGS of giant pandas, we identified several new compounds such as decenal, two isomers of decadienal, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…Analyses of perianal secretions, used by pandas to deposit scent marks, showed the presence of several fatty acids as well as some aldehydes (27,29,30). We can hypothesize on the basis of the best ligands found for our OBPs as well as on the information available for pheromone components in other mammals that both long-chain aldehydes and their corresponding carboxylic acids might represent suitable candidates.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Analyses of perianal secretions, used by pandas to deposit scent marks, showed the presence of several fatty acids as well as some aldehydes (27,29,30). We can hypothesize on the basis of the best ligands found for our OBPs as well as on the information available for pheromone components in other mammals that both long-chain aldehydes and their corresponding carboxylic acids might represent suitable candidates.…”
Section: Discussionmentioning
confidence: 79%
“…Scent marks carried by urine and perianal secretions are utilized by both sexes to advertise their presence and status (26). In female urine, short-chain fatty acids seem to be predominant (27,28), while male perianal glands contain medium and long linear aldehydes as well as a number of long-chain fatty acids together with a variety of other chemicals (29,30). At present, it is not clear which volatiles might be the best putative semiochemicals.…”
Section: Significancementioning
confidence: 99%
“…We tentatively identified compounds by searching for the library of the National Institute of Standards and Technology (NIST) and characterized each component by comparing it with the mass spectra in the library and literatures [26] . Details about the GC-MS analysis and the compounds from AGS and urine are as described by our previous papers [24,36] .…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Relatively poor in eyesight and hearing ability, pandas substantially use anogenital gland secretion (AGS) and urine to regulate their social behaviors, such as territorial advertisement, mate seeking, assessing female's reproductive status [19][20][21] . Previous behavioral and chemical assays suggest that these two sources of scent marks contain information about individual, sex, and age [22][23][24][25][26] . Both wild and captive observations reveal that pandas exhibit mate choice [27,28] .…”
mentioning
confidence: 99%
“…breeding season). Zhang et al (2008) have identified individual "odour fingerprints" in the anal gland secretions of giant pandas (Ailuropoda melanoleuca) which have been used in wild census (Zhan et al, 2006). Recognition and monitoring of individual scents can provide accurate counts of endangered species (Kerley and Salkina, 2007).…”
Section: Population Monitoringmentioning
confidence: 99%